THE PROBLEM OF CLASSIFICATION AND TYPES OF SIMILE IN MODERN LINGUISTICS - G‘ofurova Sarvaraxon; Mamasiddiqova Umidabonu (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article discusses the concept of simile has often been conflated with metaphor in various definitions, leading to terminological confusion within linguistic and literary studies. We clarify the distinct characteristics of simile as a figure of speech, arguing against the prevalent view that defines simile primarily through metaphor.